ChemInform Abstract: Deep Eutectic Solvents: Biorenewable Reaction Media for Au(I)‐Catalyzed Cycloisomerisations and One‐Pot Tandem Cycloisomerization/Diels—Alder Reactions. Issue 46 (November 2015) - Vidal, C.; Merz, L.; Garcia‐Alvarez, J.
Abstract Cycloisomerization reactions of (Z)‐enynols (I) to the corresponding furans are performed in the eutectic mixture of choline chloride/glycerol using a gold(I) complex as catalyst.